Interperiod Tax Allocation and -Depreciation Methods: Some Empirical Results. - Beaver, William H.; Dukes, Roland E. (The Accounting Review, 1973)
This article presents information on some empirical result related to tax allocation and depreciation methods. The evidence indicated that deferral earnings had the highest association with security price changes. This unexpected finding is consistent with two rather different interpretations, either the market is efficient and deferral earnings is more consistent with the underlying information set impounded in security prices, or the market is inefficient in the sense that security prices reflect only the very narrow set of reported earnings numbers. Being intolerant of ambiguity, we conducted a further analysis, which attempts to explain a result we felt to be anomalous. In fact, the ratio will be equal to the internal rate of return on the asset. The analysis reported here discards the currently prevailing views of deferred taxes as a deferred credit or deferred liability and treats tax allocation arising out of differing depreciation methods for tax and reporting purposes as a form of depreciation.